AB1167 PREGNANCY AND INFLAMMATORY ARTHROPATIES: EXPERIENCE IN A MULTIDISCIPLINARY UNIT. (2nd June 2020) - Ibarguengoitia, O.; Montero, D.; Vega, L.; García, C.; Calvo, I.; Fernandez, O.; Torre, I.; Inchaurbe, A. R.; Pérez, C.; Blanco, J. M.; Cuande, E.; Galindez, E.; et al.
Abstract : Background: Systemic inflammatory diseases are common in women at the reproductive age. These women may have fertility problems and complications during pregnancy. Objectives: To describe the experience in a multidisciplinary unit (composed of Rheumatologists and Obstetricians) and asses the complications and treatments used in patients with inflammatory diseases in a tertiary hospital compared to those registered in healthy women from the same center (preterm births 6.59%, Caesarean section (C-section) 14.4%, maternal average age 33.33 years). Methods: Retrospective and descriptive study of the evolution of pregnancy in patients with inflammatory diseases and follow-up in a multidisciplinary unit for more than 15 years (until December 2019). Demographics, maternal disease, time until conception, births, abortions, C-sections, treatments and complications were collected. Data was analyzed using IBM SPSS v23. Results: We registered 29 pregnancies (25 patients): 20 Rheumatoid Arthritis (RA), 5 Psoriatic Arthritis (PsA), and 4 Spondylarthritis (SpA). Maternal average age at diagnosis was 27.6±6.36 years and average age at childbirth/abortion 35±5.6 years. It took an average time of 8 months to conceive. 11.5% received fertility treatment using in vitro fertilization techniques. 5 abortions were registered prior to follow-up in this unit (0.2 abortions/mother). During follow-up 1 abortion (0.04 abortions/mother) was recorded in a RA patient. C-section was performed in 11 cases (39.2%): 6 RA (31.6%), 3 SpA (75%) and 2 PsA (40%). 17.2% of pregnancies were preterm (<37 weeks). Intrauterine growth restriction (IUGR) was observed in a woman (3.4%) with RA and preeclampsia was observed in 2 cases (6.9%) (RA 1, SpA 1). Disease activity (DAS28 and BASDAI) is shown in Table 1 . Treatments used prior to and during pregnancy are listed in Table 2 . 8 patients had received biological treatment prior to pregnancy (2 SpA, 6 RA)(3 Etanercept, 3 Adalimumab, 2 Certolizumab). 2 of them (RA) continued treatment during pregnancy. 1 of them discontinued it at week 17 on her own (Adalimumab) while the other continued with Certolizumab throughout pregnancy and presented IUGR. No other complications, such as infections or malformation, were observed in newborns. DAS28 data of these women can be found in Table 1 . Conclusion: In our series, as described in the literature, women with inflammatory arthropaties are older, need longer time to achieve pregnancy and have increased use of fertility techniques and increased likelihood of preterm and instrumental delivery compared to general population. Given the low number of patients receiving biological treatment no conclusions about complications and evolution of the disease can be drawn, so further investigation are needed in this group of patients. Monitoring inflammatory arthropathies in a multidisciplinary unit increases the chances of successful pregnancies. Disclosure of Interests: None declared